The Concept and Practice of Islamic Education in Realizing Peace in Society - Azhar Jaafar; Nur Rasyidah Kamaruzaman; Muhammad Idris (Muaddib: Journal of Islamic Teaching and Learning, 2025)
Hospitality and guest service in Islam represent the embodiment of noble moral values as taught in the Quran and Hadith. This study aims to explore how Islamic teachings guide individuals in hosting and serving guests. Employing a qualitative method, this research adopts the living Quran and Hadith approach, drawing data from Islamic scriptures, the results of ijtihad, and expert opinions. The use of the living Quran method is based on Engkizar's theory, tailored to the thematic needs and objectives of the study. Additional insights are supported by previous research published in reputable international journals. Thematic analysis reveals that the Islamic practices of visiting and hosting guests are not merely symbolic acts but are rooted in a profound value system encompassing etiquette, social responsibility, and mutual respect. These findings indicate that such values remain highly relevant in reinforcing a socially conscious culture grounded in Islamic principles. This study contributes to the discourse on Islamic ethics and offers insights into fostering respectful and compassionate interpersonal relationships.